Fundamental theory of coordination efficiency of signalized intersections on an arterial road - Hajime Sakakibara; Takashi Oguchi (IATSS Research, 2025)
In this study, we employed the general formula of the delay per vehicle for the case of one link at two intersections as a function of the link length and offset of traffic signals at two adjacent intersections with the general value of green splits under arbitral demand condition without oversaturation. The highest and lowest coordination efficiencies are defined for different link lengths. The nature of the link lengths and offsets that provide minimum delay per vehicle were analyzed and demonstrated. Additionally, two types of extensions to this study were conducted by determining the effects of an additional intersection located in the middle of the target link and for the installation at two adjacent intersections outside the target link.